Social and Ideological Entanglements of Preschool Education - Urszula Dzikiewicz-Gazda (University of Lower Silesia, 2012)
In this article I address a phenomenon that I call "neo-liberal entanglements" of preschool education, clearly observable in the project "Enterprising Preschooler" currently underway in Wroclaw's preschools. I provide a critical analysis of the project, exposing the ideological mechanisms that contribute to the commercialization of children's life worlds and their early socialization into the mechanisms of market consumerism.